Studi Literatur Pengaruh Pemberian Zinc Terhadap Status Gizi Pada Anak-Anak - Melita Tanjung; William Wibowo; Gracia Winaktu; Marina Rumawas (Jurnal MedScientiae, 2023)
During childhood, rapid growth occurs so that adequate intake is needed to grow optimally, but low appetite is one of the problems often faced. Based on data from WHO (2017), Indonesia is the third country with the highest prevalence of stunted toddlers in Southeast Asia with an average of 36.4% in 2005-2017. One of the causes of lack of appetite and nutrition is zinc deficiency. Therefore, this study review aims to analyze the effect of zinc administration on nutritional status in children. Literature searches were conducted on several databases, namely Pubmed, Google Scholar, and the National Library of Indonesia website. The keywords used were "zinc", "appetite", "children" and 10 journals from 2011 to 2020 were obtained for review. The inclusion criteria were journals from the last 10 years, zinc affecting appetite, and children aged 6 months - 12 years. Administration of 10 mg zinc per day for at least 12 - 24 weeks and a child's serum zinc level of <75 μg/dL had a significant appetite enhancing effect. Zinc supplementation can increase the total intake of calories, carbohydrates, protein, and fat leading to an increase in weight, height, body mass index, and nutritional status of children.